Analysis Influence of Financial Performance on Economic Growth Study on Regencies and Cities in Southern Sumatra - Muhammad Riski Saputra; Retno A. Ekaputri (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
The purpose of this study is to investigate the impact of financial performance on economic growth in districts/cities in southern Sumatra between 2018 and 2022. Regional financial performance is measured using the independence ratio and statistics on local original income and government support., the effectiveness ratio using revenue realization data and revenue targets, as well as efficiency ratios using data on costs incurred and actual revenues and the impact on economic growth will be measured by taking a sample of 60 districts/cities in southern Sumatra (in 5 provinces: Sumatra Selatan, Bengkulu, Jambi, Bangka Belitung, and Lampung). Secondary data from BPS publications, specifically GRDP and Regional Income and Expenditure Budget (APBD) statistics from the Indonesian Ministry of Finance in 60 districts/cities in southern Sumatra, were used in this study. Panel data combines cross-sections and time series for analysis. For econometric testing, the t-test and the standard assumption test are used, whereas the random effects model is assessed using the Lagrange Multiplier test (LM Test). The F test is used to investigate the influence of factors in part. The coefficient of determination (R2) test is used to examine the ability of the regression model to explain fluctuations in the dependent variable by testing the influence of variables at the same time. The research results show that (1) Financial performance in the form of effectiveness ratios and efficiency ratios has a positive effect on economic growth. (2) Financial performance in the form of the independence ratio hurts economic growth.